Using the UMLS to represent medical curriculum content. - Kanter, S. L. (American Medical Informatics Association, 1993)
Recent innovations in medical education have highlighted the need for faculty involved with the curriculum to carefully examine curricular content with goals of detecting omissions and unwanted redundancies of subject matter, adding and integrating new content, and deleting old content. A number of medical schools have attempted to deal with these issues by developing a database of curricular content information, most often using faculty- or student-selected keywords to represent each unit of instruction. However, several problems have been identified with this method, and achieving the goals mentioned above remains a formidable task. This paper outlines an alternative method that uses the resources of the UMLS to characterize a medical concept by the semantic types of its co-occurring terms. This approach can facilitate achievement of the aforementioned goals.